2011
DOI: 10.1029/2010gb003850
|View full text |Cite
|
Sign up to set email alerts
|

An updated climatology of surface dimethlysulfide concentrations and emission fluxes in the global ocean

Abstract: [1] The potentially significant role of the biogenic trace gas dimethylsulfide (DMS) in determining the Earth's radiation budget makes it necessary to accurately reproduce seawater DMS distribution and quantify its global flux across the sea/air interface. Following a threefold increase of data (from 15,000 to over 47,000) in the global surface ocean DMS database over the last decade, new global monthly climatologies of surface ocean DMS concentration and sea-to-air emission flux are presented as updates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
944
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(1,075 citation statements)
references
References 84 publications
(149 reference statements)
67
944
12
Order By: Relevance
“…The maximum DMS concentrations we report (255 nmol L − 1 ) were similar to maximum values reported by other studies in coastal near-shore areas of the North Sea (Kwint and Kramer, 1996;van Duyl et al, 1998) and were higher than those reported in the deeper and seasonally stratified northern North Sea, with maximum DMS values of 5 nmol L − 1 reported during a bloom of coccolithophores (Archer et al, 2002). Overall, the DMS maximum concentrations in the near-shore coastal areas of the North Sea are one to two orders of magnitude higher than the seasonal maxima typical of open oceanic waters, as compiled and reviewed by Lana et al (2011).…”
Section: Seasonal Evolution Of Chl-a and Dms(po) Concentrationmentioning
confidence: 65%
“…The maximum DMS concentrations we report (255 nmol L − 1 ) were similar to maximum values reported by other studies in coastal near-shore areas of the North Sea (Kwint and Kramer, 1996;van Duyl et al, 1998) and were higher than those reported in the deeper and seasonally stratified northern North Sea, with maximum DMS values of 5 nmol L − 1 reported during a bloom of coccolithophores (Archer et al, 2002). Overall, the DMS maximum concentrations in the near-shore coastal areas of the North Sea are one to two orders of magnitude higher than the seasonal maxima typical of open oceanic waters, as compiled and reviewed by Lana et al (2011).…”
Section: Seasonal Evolution Of Chl-a and Dms(po) Concentrationmentioning
confidence: 65%
“…Labeled DMS ( 13 C-DMS) was added to the bags at a final concentration of 6 nmol L À1 in order to directly assess the origin of CH 4 production from organic labeled compounds. The 13 C-DMS tracer additions was estimated to be close to 30-100% of ambient concentrations in surface waters which could fluctuated from <5 to 15 nmol L À1 in upwelling areas according to Andreae (1985) and Lana et al (2011). In this study, DMS levels in seawater were not measured.…”
Section: Experimental Assaysmentioning
confidence: 99%
“…Ocean salinity is taken from the monthly climatology of the World Ocean Atlas 2001 . Oceanic concentrations of DMS are a monthly climatology from Lana et al (2011). Isoprene concentrations in the ocean are calculated using the parameterization of Broadgate et al (1997), relating isoprene and chlorophyll concentrations, here with chlorophyll prescribed as a monthly climatology from the World Ocean Atlas 2001 .…”
Section: Ocean-to-atmosphere Fluxesmentioning
confidence: 99%